The discursive construction of agri-food heritage in contemporary societies: conceptual approaches and theoretical debates - Blas-Yañez, Sandra; Thomé-Ortiz, Humberto; Espinoza Ortega, Angélica; Vizcarra Bordi, Ivonne (Revista Mexicana de Ciencias Agrícolas, 2018)
This essay addresses the three theoretical perspectives that have examined the agri-food heritage in the last 10 years. The objective was to identify and contrast the different positions, as well as to adopt different angles to address the agri-food heritage from rural studies. The forms of social approach that have contributed to the formation of a theoretical corpus on the agri-food heritage, are diverse, maintain contrasting approaches and before the discursive practice of their institutional precepts, generate considerable changes in the forms of appropriation, production, distribution and consumption of agrifood resources. For this reason, it is proposed to develop an interpretative theoretical framework through phenomenology, which accounts for the flows and relationships between discursive dimensions, which impact on the resignification of value, positioning and consumption of emblematic agro-food products by contemporary society. In addition, to contribute to giving voice to a type of emerging discourse, based on local dynamics, which articulate the appropriation of the various patrimonial discourses and the existing negotiations between the local and the global.
Keywords: counter-discourse; heritage studies; phenomenology